Liquidity Ratios of Polish Commercial Banks - Pavla Vodová (European Financial and Accounting Journal, 2013)
As liquidity problems of some banks during global financial crisis reemphasized, liquidity is very important for functioning of financial markets and the banking sector. The aim of this paper is therefore to evaluate comprehensively the liquidity positions of Polish commercial banks via five different liquidity ratios in the period of 2001– 2011 and to find out whether the strategy for liquidity management differs by the size of the bank. The results enable us to conclude that liquidity of Polish banks has decreased in recent years, partly as a result of higher lending activity but mainly due to the financial crisis. Almost all Polish banks are sensitive to potential massive deposit withdrawals. Only some banks finance their lending activity by deposits; most banks are dependent on other sources of finance. Large and medium sized banks rely on the interbank market or on a liquidity assistance of the Lender of Last Resort, small banks hold buffer of liquid assets.
Keywords: G01; G21; 650; Liquidity risk; Liquidity ratio; Commercial banks.